2020
DOI: 10.1016/j.bpj.2020.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Regulated Outside-In Activation of an I-Domain-Containing Integrin

Abstract: Integrins are heterodimeric transmembrane proteins that mediate cellular adhesion and bidirectional mechanotransductions through their conformational allostery. The allosteric pathway of an I-domain-containing integrin remains unclear because of its complexity and lack of effective experiments. For a typical I-domain-containing integrin a X b 2 , molecular dynamics simulations were employed here to investigate the conformational dynamics in the first two steps of outside-in activation, the bindings of both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Several studies have reported that force promotes integrin conformational activation by governing the transition from bent to extended conformations [ 44 , 50 , 108 , 113 , 114 , 115 , 116 ]. The main structural modifications that integrins undergo during conformational activation have been identified; however, the exact mechanisms by which force promotes the changes in integrin conformation are poorly understood.…”
Section: The Effects Of Force On Integrin Conformationmentioning
confidence: 99%
“…Several studies have reported that force promotes integrin conformational activation by governing the transition from bent to extended conformations [ 44 , 50 , 108 , 113 , 114 , 115 , 116 ]. The main structural modifications that integrins undergo during conformational activation have been identified; however, the exact mechanisms by which force promotes the changes in integrin conformation are poorly understood.…”
Section: The Effects Of Force On Integrin Conformationmentioning
confidence: 99%